The inspiration of Bauhaus principles on the modern housing in Cyprus - Mustafa Aziz Amen (Alanya Hamdullah Emin Paşa Üniversitesi, 2017)
Modern architecture developed more than a century ago to find solutions suitable to solve the new concerns of the industrial revolution that changed the social idea of the world in all aspects. Bauhaus school which established by Walter Gropius in 1919 adopted too many principles and ideas that were totally new to the architectural concept and theory at that time; their principles started from Simplicity, Angularity, Abstraction, Consistency, Unity, Organization, Economy, Subtlety, Continuity, Regularity, and Sharpness. Those principles affected the architectural world and found its way through many applications in different parts of the world. The unlimited space or the international space that had a significant influence on the architecture space and form as well as the introduction of the new material, the anti- decorating, and Platonic forms had worked to reconstruct the architecture in the world. Cyprus as an island close to the sources of the movement got the influence from the modern movement. The study will concentrate on Efruz Housing which designed by Ahmet Vural, who developed the project in the 60th of the last century. The aim of the research is to find the relationship and effects of Bauhaus school in Cyprus through studying and analyzing some of Ahmet Vural works. The methodology will depend on a comparison with the traditional housing that preceded Mr. Vural work and how the Modernism changed the main features of the housing on the Island.